TRACE-ELEMENT PARTITIONING IN OLIVINE: MODELLING OF A COMPLETE DATA SET FROM A SYNTHETIC HYDROUS BASANITE MELT - Zanetti A.; Tiepolo M.; Oberti R.; Vannucci R. (My University, 2004)
Olivine/liquid partition coefficients for most trace elements relevant in petrogenetic studies are provided for a hydrous basanite melt equilibrated at 1.4 GPa and 1055 °C. The partitioning results determined by a combination of EMP and SIMS analyses are discussed in terms of available crystal-chemical mechanisms and crystal-structure control. The critical evaluation of this data set and of those reported in the literature, in the frame of the present lattice-strain model, provides useful suggestions for future studies designed to clarify incorporation mechanisms and site preference in olivine. A further useful suggestion is that the measured Ol/LD values for Li, Mg and Sc allow a straightforward but reliable estimate of the D0 for 1+, 2+ and 3+ cations, respectively. The assessment of D0 for VIHFSE4+ is probably biased by their partitioning between the T and M sites. Anyway, it can be reasonably assumed to be close to Ol/LDZr.
Keywords: Partition coefficients; Olivine; Hydrous basanite; Trace elements; SIMS analysis